Investigation of hot stamping process parameters in up & down machining on ABS materials under quality purposes of different stamping processes - (:unkn) unknown (Certex, INCDTP-ICPI, 2016)
Hot stamping foil manufacturers have been introducing only an average setting parameters gap. They are requesting that the end users find their most suitable and specific settings by changing parameters with numerous trial processes. Key parameters in machining for a hot stamping process are: die & sample temperature, dwell time and pressure; and these three variables should be proportional with each other. ABS (Acrylonitrile Butadiene Styrene) is one of the most common thermoplastic polymers in the hot stamping industry. A large quantity of identical ABS material, which is used as a water dispenser part by an international brand- Arçelik A.S¸., was ordered. In addition, this was accompanied by multiple types of hot stamping foils which are suitable for use on ABS materials. These foils have different structures and release layers and were chosen and supplied for the experiments. More than one thousand experiments were performed. The most correct parametric values were determined for each targeted pattern foils. Additional tests were performed to determine feasible end-users' harms; moreover, various failures also occurred and these failures were examined. Every result was analysed and compared with their detailed technical photos and graphs. A guide for the industry was established which would establish a new course to help machining operators reach the solution more quickly and easily, in case they have a process mistake. © 2016 Certex, INCDTP-ICPI.
Keywords: ABS material; Hot Stamping foil; Silicone die